Exploring the culinary heritage: Strategies for promoting gastronomy tourism in Tourism Village Tista Tabanan - I Nyoman Cahyadi Wijaya; I Ketut Budarma; Ni Gst Nym Suci Murni (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This study explores strategies to promote local cuisine as a central element of gastronomy tourism in Tista Tourism Village, inspired by the UNWTO's recognition of Ubud in 2019. Using qualitative research methods, this study merges the Triangle of Indonesian Gastronomy theory with Local Cuisine Development principles. Subsequent data analysis employed qualitative descriptive methods, IFAS matrix, EFAS matrix, and SWOT analysis. The evaluation of the internal-external matrix (IE) pinpointed the recommended strategy of elevating local cuisine into a central offering of gastronomy tourism, situated within cell I. This conclusion finds support in the IFE score of 3.3 and EFE score of 3.02. Emphasizing cultural and historical aspects, this approach involves crafting narratives that connect local cuisine to its origins. The SWOT analysis yields four strategies focusing on preserving cultural heritage and enhancing existing attractions for an enriched gastronomy tourism experience, this research enhances gastronomic tourism in Tista Tourism Village and provides a strategic framework for stakeholders which supports sustainable development by leveraging strengths, addressing weaknesses, and mitigating potential threats. Active community engagement fosters ownership and participation are vital findings to enhance the initiative's enduring success, to conclude The study's critical findings are that entities such as the local community, POKDARWIS, and Village authorities have the sense of active engagement to nurture a sense of ownership and participation as it is crucial for the enduring success 0f gastronomy tourism.